2000
DOI: 10.1128/jvi.74.15.7048-7054.2000
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccines Encoding Viral Glycoproteins Induce Nonspecific Immunity and Mx Protein Synthesis in Fish

Abstract: Protective immunity by vaccination with plasmid DNA encoding a viral glycoprotein (G) has long been assumed to result from the induction of a specific immune response. We report here that the initial protection may be due to the induction of alpha/beta interferon, with long-term protection due to a specific response to the encoded viral G. DNA vaccines encoding the Gs of three serologically unrelated fish rhabdoviruses were used to vaccinate rainbow trout against a lethal challenge with infectious hematopoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
3
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(100 citation statements)
references
References 45 publications
(38 reference statements)
5
91
3
1
Order By: Relevance
“…Interestingly and significantly, an IHNV DNA vaccine could provide significant protection as soon as 4 d after intramuscular injection (LaPatra et al, 2001b). This early, nonspecific antiviral protection was shown to be associated with an induced type I IFN response in rainbow trout Oncorhynchus mykiss (Kim et al, 2000). The type I IFNs of rainbow trout have also been shown possess antiviral activities against viral hemorrhagic septicemia virus (VHSV) (Zou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly and significantly, an IHNV DNA vaccine could provide significant protection as soon as 4 d after intramuscular injection (LaPatra et al, 2001b). This early, nonspecific antiviral protection was shown to be associated with an induced type I IFN response in rainbow trout Oncorhynchus mykiss (Kim et al, 2000). The type I IFNs of rainbow trout have also been shown possess antiviral activities against viral hemorrhagic septicemia virus (VHSV) (Zou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to express proteins of disease agents with the greatest possible similarity to the authentic molecule so that the proper immune response is induced when the proteins are used as a vaccine. Baculovirus expression systems are effective for properly modifying recombinant proteins so they are antigenically, immunogenically, and functionally similar to the native protein (Kim et al, 2000).…”
Section: Recombinant Inactivated Vaccinesmentioning
confidence: 99%
“…That success story is proof of the tremendous potential of vaccination and has led to the development of vaccines against almost all infectious agents affecting people and animals. The ultimate objective of vaccination is to induce an immune response that subsequently recognizes the infectious agent and fights off the disease (Kim et al, 2000).…”
Section: Literature Review History and Overview Of Vaccine Developmentmentioning
confidence: 99%
“…It has also been reported that an antigenic determinant of the glycoprotein gene of IHNV expressed as fusion protein with trpE protein of Escheri chia coli induced protective immunity (Gilmore et al, 1988). Recent studies on DNA vaccines for fish rhab dovirus glycoprotein also shown that the glycoprotein is sufficient to induce protective immunity against the cor responding virus and even other rhabdoviruses in the same genus (Corbeil et al, 1999;Kim et al, 2000).…”
mentioning
confidence: 99%
“…However, a recent development in molecular biology has made it possible to produce a large amount of recombinant viral protein as a sub-unit vaccine that can be used for vacci nation by immersion or injection of individual fish (Munn, 1994;Lorenzen, 1999). In addition, viral genes cloned into an expression vector and introduced into fish tissue as DNA vaccines have been proved to be effective in in door experiments and small-scale field experiments (Corbeil et al, 1999;Kim et al, 2000).…”
mentioning
confidence: 99%